2000
DOI: 10.1515/bc.2000.064
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases-2, -3, -7, -9 and -10, But Not MMP-11, Are Differentially Expressed in Normal, Benign Tumorigenic and Malignant Human Keratinocyte Cell Lines

Abstract: In order to investigate the correlations between constitutive proteinase expression and the degree of tumorigenicity of cancer cells we have studied a model system of three keratinocyte cell lines. RT-PCR studies showed that the cell lines express the genes of matrix metalloproteinase-2, -3, -7, -9, -10 and -11, indicating that they are able to synthesize the corresponding enzymes. Actual MMP synthesis was proven by zymography and Western blotting. In conditioned media gelatinolytic activities or immunoreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 21 publications
2
43
0
1
Order By: Relevance
“…Elevated expression levels of MMP-9 are strongly correlated with malignant phenotype in SCC [34] and are characteristic of malignant transformation of cells [29]. In human keratinocyes constitutive production and secretion of MMP-9 correlate with the degree of tumorigenicity in malignantly transformed clones [33]. Thus, the dramatically increased secretion of MMP-9 observed in As-TM cells might be an important biomarker for arsenicinduced malignant transformation in human keratinocytes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Elevated expression levels of MMP-9 are strongly correlated with malignant phenotype in SCC [34] and are characteristic of malignant transformation of cells [29]. In human keratinocyes constitutive production and secretion of MMP-9 correlate with the degree of tumorigenicity in malignantly transformed clones [33]. Thus, the dramatically increased secretion of MMP-9 observed in As-TM cells might be an important biomarker for arsenicinduced malignant transformation in human keratinocytes.…”
Section: Discussionmentioning
confidence: 97%
“…MMPs are a family of matrix-degrading enzymes that play a critical role in invasion and metastasis of malignant tumors and hypersecretion of MMPs is common in highly aggressive tumors [33]. MMP-9 specifically targets type IV collagen, a major component of basement membrane, and appears to play a crucial role in tumor invasion across the basement membrane [34].…”
Section: Discussionmentioning
confidence: 99%
“…When co-cultured with stromal fibroblasts malignant II-4 cells up-regulated MMP-1 and MMP-9 production while no up-regulation was found in benign A5 cells. In this study it was hypothesized that this reciprocal up-regulation of proteases between cancer cells and fibroblasts was likely to be mediated by soluble factors secreted by the cancer cells (Bachmeier et al, 2000). A more recent study showed that co-culture of non-malignant HaCaT cells with fibroblasts induced MMP-2 activation, an invasive phenotype and proteolysis of the ECM (Laeeq and Faust, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…12,13 The antibody has been already successfully used by other research groups. 15,16 It is produced continuously and will be provide for free to the scientific community upon request to Dr. Lichtinghagen. Thus, the antibody is well established and will be available to the research community in the future.…”
Section: Discussionmentioning
confidence: 99%